ISLAMIC RELIGIOUS EDUCATION CURRICULUM FROM THE PERSPECTIVE OF IMAM AL-GHAZALI AND ITS RELEVANCE IN THE 21ST CENTURY - Muhammad Faizin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The curriculum in the world of education is a learning plan that will be explained to students in one semester, such as the examples that have been arranged in lesson plans, lesson plans, and lesson plans, each of which has activities or activities in the learning process with the intention of achieving certain goals. One of the important figures in Islamic education is Imam Al-Ghazali. He is a thinker who gives many of his thoughts for the development of the progress of human life and has various kinds of well-known writings. He has ideas related to the concept of a science curriculum which is divided into three basics, namely based on field, based on object and based on legal status. The educational curriculum that he implemented in Islamic education has a number of features that can be used as good references and guidelines in implementing the educational curriculum in the 21st century. So it is not uncommon for many educational centers to use the educational curriculum concept from Al-Ghazali's perspective. So, based on this phenomenon, we took the initiative to examine further the relevance of the educational curriculum from the perspective of Imam Al-Ghazali to the 21st century education curriculum. Apart from knowing Al-Ghazali's thoughts regarding the Islamic education curriculum, this article also aims to find out the relevance of the educational curriculum from his perspective. and its relevance to education in the 21st century.